2014
DOI: 10.2319/030414-152.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional genioplasty in growing patients

Abstract: Objective: To evaluate the role of age as a moderator of bone regeneration patterns and symphysis remodeling after genioplasty. Method: Fifty-four patients who underwent genioplasty at the end of their orthodontic treatment were divided into three age groups: younger than 15 years at the time of surgery (group 1), 15 to 19 years (group 2), and 20 years or older (group 3). Twenty-three patients who did not accept genioplasty and had a follow-up radiograph 2 years after the end of their orthodontic treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The amount of new bone formation and the extent of remodeling around the repositioned chin is greater than in the case it is performed after the age of 15 (Chamberland et al, 2015). Therefore, when indicated for cosmetic concerns, it appears useless to wait for a later age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of new bone formation and the extent of remodeling around the repositioned chin is greater than in the case it is performed after the age of 15 (Chamberland et al, 2015). Therefore, when indicated for cosmetic concerns, it appears useless to wait for a later age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when indicated for cosmetic concerns, it appears useless to wait for a later age. It improves facial aesthetics, which can be a serious psychosocial handicap, even early in life (Chamberland et al, 2015). It allows redirection of mandibular growth reducing the open bite in wide angle class II patients (Precious and Delaire, 1985;Frapier et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that genioplasty is the most stable of the orthognathic surgery procedures and that significant relapse is almost never observed. 49,51,57,58 In contrast, few reports noted some greater relapse in younger patients when compared to adults but it was neither clinically nor statistically significant. 50 The use of expensive bone screws may not be required for all genioplasty procedures to achieve better postsurgical stability 59 since it can be expected with the use of wire fixation.…”
Section: Jcdpmentioning
confidence: 95%
“…Some studies showed better healing after surgery in young patients following this type of surgery. 49,50 Other reports found that after genioplasty, bone remodeling of the mandibular alveolar bone above and behind the osteotomy site increased when this surgery is done in young growing patients. [51][52][53][54][55][56] On the contrary, there are some concerns about possible negative effects of the early surgery on growth postoperatively and decreased stability would be a major reason for waiting until little or no growth remained.…”
Section: Chin Deformitiesmentioning
confidence: 99%
See 1 more Smart Citation